2022
DOI: 10.1111/ajad.13258
|View full text |Cite
|
Sign up to set email alerts
|

Sexual minority disparities in opioid and benzodiazepine misuse among adults with opioid use disorder

Abstract: Background and Objectives Sexual minority individuals demonstrate disparate rates of substance use. Research suggests that bisexual women are vulnerable to substance use disorders when compared to other sexual minority groups. This study explored differences in prevalence of past‐year alcohol use disorder (AUD) with and without concurrent past‐year opioid and/or benzodiazepine misuse. Methods The present study utilized responses from the National Survey on Drug Use and Health (NSDUH) public dataset between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…This finding is consistent with previous findings of bisexual individuals reporting higher odds of opioid misuse 34 and Lesbian/Gay/Bisexual groups experiencing higher pain reliever misuse relative to heterosexual individuals 35 . It is also reported that bisexual females are more likely to co‐use opioids and benzodiazepines among adults with opioid use disorder 36 . However, the findings of Bisexual individuals misusing benzodiazepines and both drugs are novel.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is consistent with previous findings of bisexual individuals reporting higher odds of opioid misuse 34 and Lesbian/Gay/Bisexual groups experiencing higher pain reliever misuse relative to heterosexual individuals 35 . It is also reported that bisexual females are more likely to co‐use opioids and benzodiazepines among adults with opioid use disorder 36 . However, the findings of Bisexual individuals misusing benzodiazepines and both drugs are novel.…”
Section: Discussionsupporting
confidence: 90%
“…35 It is also reported that bisexual females are more likely to co-use opioids and benzodiazepines among adults with opioid use disorder. 36 However, the findings of Bisexual individuals misusing benzodiazepines and both drugs are novel. The individuals who are Bisexual are more likely to experience anxiety, depression, and higher rates of trauma compared with their heterosexual counterparts which are risk factors for misuse of prescription drugs as well as for selfmedication.…”
Section: Resultsmentioning
confidence: 99%
“…Conceptualizations of the risk environment and structural vulnerability guided the selection of indicator variables used to define the latent classes [ 33 37 , 42 , 43 ]. Sociodemographic characteristics (sex, race/ethnicity, age, sexual orientation, and housing status) were selected, recognizing (a) how race, gender identity, sexual orientation, age, and housing status shape the risk environment [ 33 37 , 44 46 ], (b) disproportionate overdose mortality rates among racial and ethnic minorities and homeless adults [ 47 , 48 ], and (c) disparities in treatment access for substance use and infectious diseases [ 49 , 50 ]. Preferences related to injection equipment were also included because (a) larger syringes are often used by individuals with longer histories of substance use because of scar tissue and overall vein health [ 51 ] and (b) shorter needles can be used for skin popping and injecting into the hands, feet, and superficial veins, all of which can increase the risk of abscesses and skin and soft tissue infections [ 51 , 52 ].…”
Section: Methodsmentioning
confidence: 99%